2018
DOI: 10.1097/mlr.0000000000000786
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of 2 Constituencies

Abstract: Background:Patient and clinician stakeholders are inadequately engaged in key aspects of research, particularly regarding use of Big Data to study and improve patient-centered outcomes. Little is known about the attitudes, interests, and concerns of stakeholders regarding such data.Research Design:The New York City Clinical Data Research Network (NYC-CDRN), a collaboration of research, clinical, and community leaders built a deidentified dataset containing electronic health records from millions of New Yorkers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…http://jme.bmj.com/ J Med Ethics: first published as 10.1136/medethics-2019-105651 on 12 November 2019. Downloaded from Concerns that data could not truly be deidentified 32 If data sharing is motivated by financial gain or profit 20…”
Section: Perceived Benefits Of Data Sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…http://jme.bmj.com/ J Med Ethics: first published as 10.1136/medethics-2019-105651 on 12 November 2019. Downloaded from Concerns that data could not truly be deidentified 32 If data sharing is motivated by financial gain or profit 20…”
Section: Perceived Benefits Of Data Sharingmentioning
confidence: 99%
“…Central role of clinicians in introducing patients to research 32 options and more efficient use of resources. Patients seem to also value the potential of (direct) personal health benefits.…”
Section: Support Of Research In General (86%) 16mentioning
confidence: 99%
“…The NYC Clinical Data Research Network modified its engagement strategies to facilitate involvement of people with limited trust and found lack of trust to be associated with concerns about data privacy and security, and lack of confidence that findings would be shared with the community. 2 Within PCORnet, most networks identified trust as essential to achieving high levels of engagement and the need to build and nurture trust was clear. 3 The recurring themes of trust and trustworthiness in public engagement also highlights the gap in our knowledge related to the underpinnings of trust in community-academic relationships, the need to measure, track, and improve trust, and the responsibility of researchers to become more trustworthy.…”
mentioning
confidence: 99%
“…Further, little is known about patient engagement in the context of large teams or networks. Most of the literature that exists comes from research conducted in the U.S. and is descriptive in nature, highlighting reflections on challenges, successes, and methods used to evaluate engagement [12][13][14][15][16][17][18][19]. One study in the U.S. systematically evaluated the engagement experiences of patient-partners in a patient-oriented research network and identified facilitators of engagement such as communicating clear expectations and assessing engagement on a regular basis [20].…”
Section: Introductionmentioning
confidence: 99%